HOW TEXTBOOK AFFECT LEARNING: THE REPRESENTATION OF MULTIPLE INTELEGENCE IN SCHOOL TEXTBOOK - Winny Liliawati; Fida Hanifah (Jurnal Pengajaran MIPA, 2019)
This research aims to know the representation of multiple intelligence types in physics textbooks for Junior High School. The data source of this research is the BSE Science (physics subject matters) textbook adapted from 6 books, such as a book for VII grade levels 1 and 2, a book for VIII grade levels 1 and 2, and a book for IX grade level 1 and 2. This research uses using a qualitative descriptive method by analyzing textbooks using by checklist system instrument, which had developed by Seyyed Ayatollah Razmoo and Zahra Jozaghi (2010). This checklist system refers to 8 multiple intelligence types by Howard Gardner (1999). These eight intelligence types would be specified in several activities related to each type. The data analysis result shows that the physics subject of Science in the BSE textbook for Junior High School is more centered around logical intelligence, which is intended for an experiment, collecting data, logical thinking, and numerical calculation. Therefore, it can be concluded that the book has not accommodated the entire intelligence.